Dynamics of Small Non-coding RNA Profiles and the Intestinal Microbiome of High and Low Weight Chickens - Zhou, Hao; Yang, Lingyu; Ding, Jinmei; Xu, Ke; Liu, Jiajia; Zhu, Wenqi; Zhu, Jianshen; He, Chuan; Han, Chengxiao; Qin, Chao; Luo, Huaixi; Chen, Kangchun; et al. (Frontiers in Microbiology, 2022)
The host and its symbiotic bacteria form a biological entity, holobiont, in which they share a dynamic connection characterized by symbiosis, co-metabolism, and coevolution. However, how these collaborative relationships were maintained over evolutionary time remains unclear. In this research, the small non-coding RNA (sncRNA) profiles of cecum and their bacteria contents were measured from lines of chickens that have undergone long-term selection for high (HWS) or low (LWS) 56-day body weight. The results from these lines that originated from a common founder population and maintained under the same husbandry showed an association between host intestinal sncRNA expression profile (miRNA, lncRNA fragment, mRNA fragment, snoRNA, and snRNA) and intestinal microbiota. Correlation analyses suggested that some central miRNAs and mRNA fragments had interactions with the abundance of intestinal microbial species and microbiota functions. miR-6622-3p, a significantly differentially expressed (DE) miRNA was correlated with a body weight gain related bacterium, Alistipes putredinis. Our results showed that host sncRNAs may be mediators of interaction between the host and its intestinal microbiome. This provides additional clue for holobiont concepts.